(untitled) (Journal of Bangladesh Academy of Sciences, 2013)
Transparency loss and excess excitation loss are responsible for relatively lower conversion efficiency of single junction solar cell. One way to reduce these two losses is to use multijunction solar cell. In this research InxGa1-xN based single, double and triple junction solar cells were simulated employing AMPS-1D simulator. The band gap of each layer depends on the composition percentage of InN and GaN within InxGa1-xN. In this simulation the authors found 24.51, 33.89, and 42.12% efficiencies for single, double and triple junctions, respectively. DOI: http://dx.doi.org/10.3329/jbas.v37i1.15682 Journal of Bangladesh Academy of Sciences, Vol. 37, No. 1, 65-72, 2013